Facile synthesis N-doped hollow carbon spheres from spherical solid silica - Wenelska, Karolina; Ottmann, Alexander; Schneider, Philip; Klingeler, Rüdiger (Journal of colloid and interface science, 2018)
Nitrogen-doped core/shell carbon nanospheres (NHCS are prepared and their capability as an anode material in lithium-ion batteries is investigated. The synthesis methodology is based on a fast template route. The resulting molecular nanostructures are characterized by X-ray diffraction, transmission electron microscopy, thermal analysis, and nitrogen adsorption/desorption measurement as well as by cyclic voltammetry and galvanostatic cycling. The core/shell structure provides a rapid lithium transport pathway and boasts a highly reversible capacity. For undoped HCS the BET specific surface area is 623m2/g which increases up to 1000m2/g upon N-doping. While there is no significant effect of N-doping on the electrochemical performance at small scan rates, the doped NHCS shows better specific capacities than the pristine HCS at elevated rates. For instance, the discharge capacities in the 40th cycle, obtained at 1000mA/g, amount to 170mAh/g and 138mAh/g for NHCS and HCS, respectively.